Pengaruh Proses Equal Channel Angular Pressing Terhadap Sifat Mekanik Aluminium Silikon Dengan Suhu Anil 300°C - Doni Eka Phutra.D; Yulfitra Yulfitra (Fakultas Teknik UMSU, 2018)
The aim of this study to study the effect of the Equal Channel Angular Pressing process the mechanical properties of aluminum silicon with annealing temperature of 300 ° C. An aluminum silicon rod with a length of 40 mm and a width of 9.5 mm in diameter is passed to the ECAP mold with a mold flow angle of 120 °. Material hardness and microstructure of materials before and after the ECAP process are examined and compared. The results showed that after the ECAP process, the hardness of aluminum silicon in the longitudinal section increased and was fairly evenly distributed, ie, at annealing time of 10 minutes the hardness value was 54.30 BHN, at 15 minutes resistance the hardness increased to 55.08 BHN and 25 minutes the hardness value rose to 55.69 BHN, as well as the microstructure showed that the longer the time annealed, the finer the grains on silicon aluminum.